Studies on gene ARR expression - Gianniosis, Mary (My University, 2008)
ABSTRACT Rifampicin is a major chemotherapeutic agent used against mycobacterial and nocardial infections. High level resistance is primarily due to mutational alterations in the rpoB gene encoding the β subunit of RNA polymerase. When challenged, these bacteria may inactivate rifampicin by one of four mechanisms: decomposition, ADP-ribosylation, glucosylation and phosphorylation. ADPribosylation occurs in many mycobacterial pathogens but nothing is known about the properties of the enzyme responsible. Consequently mutational analysis may be used to explore structure-function relationships in this protein. Three mutants with changes in the open reading frame were selected and studied. The altered arr gene in pMG1 was obtained by in vivo selection whilst in pMG2 and pMG4 by in vitro mutagenesis. The mutated arr gene in pMG1 and pMG2 conferred resistance to 50 μg/ml of rifampicin while in pMG4 to 200 μg/ml. This suggested that alterations near the N-terminus resulted in lowered activity because of closer proximity to the active site. This is the first successful report of induced arr gene expression. This over-expression of the Arr ADP-ribosyltransferase and its mutants assisted in their later purification by metal affinity chromatography.
Keywords: Over-expression and purification of ADP-ribosyltransferase that inactivates Rifampicin by ribosylation